Identifying Determinants of Social Media Influence on Purchase Decisions: A Factor Analytical Study of Rural Consumers in Selected Districts of Uttar Pradesh - Ahmad, Anas; Singh, Neeraj Kumar; Ahmad, Sultan; Fatima, Rafat; Alam, Aftab; Ghani, Usman (International Review of Management and Marketing, 2026)
This study investigates the key determinants influencing social media’s impact on purchase decisions among rural consumers in selected districts of Uttar Pradesh, India. With the rapid penetration of smartphones and internet services in rural areas, social media platforms have emerged as significant influencers in shaping consumer preferences. The research adopts a descriptive and exploratory design, collecting primary data from 241 respondents across Lucknow, Kanpur, Agra, Jhansi, and Gorakhpur. A structured questionnaire comprising 25 items was employed to measure five latent factors— Content and Informativeness, Trust and Credibility, Peer Influence, Emotional Engagement, and Convenience—adapted from validated scales. The data was analysed using Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) to test reliability, validity, and model fit. The results indicate that all five factors significantly influence rural consumers’ purchase intentions, with Trust, Informativeness, and Convenience being particularly strong predictors. The findings reinforce the importance of trust-building, peer validation, and emotional engagement in digital marketing strategies targeting rural markets. Additionally, the study offers practical insights for marketers, suggesting that culturally localized and emotionally engaging content can enhance engagement and conversion rates in rural settings. However, the study is geographically limited to five districts and employs cross-sectional data, suggesting a need for further research with broader samples and longitudinal analysis. Overall, this study contributes to the limited literature on rural consumer behaviour and provides a strategic framework for effectively leveraging social media in rural India.